PENGUATAN KARAKTER REMAJA MENGGUNAKAN MEDIA WAYANG CAKRIK BATIK - Widagdo, Muhammad Bayu; Luqman, Yanuar (Master of Communication Science Program, Universitas Diponegoro, 2021)
The popularity of puppets and batik in the eyes of teenagers, especially Javanese people, is already inferior to fictional Hollywood superhero figures such as Hulk, Superman, Batman, Ironman, Spiderman, and other Avenger. On the other hand, we actually have a wealth of traditional art forms that are very rich in philosophical values and unmatched artistic techniques. However, nowadays, youth's pride in the nation's art works seems fragile and easily outdated, being replaced by an external art culture that is full of modernity and relatively superficial in value. The redesign of the wayang cakrik batik from the wayang kulit reference object is an effort to strengthen the national identity of the youth, while at the same time offering a solution so that the youth will love and be proud of the art of their ancestral heritage. This survey research with a quantitative descriptive approach seeks to evaluate and capture the responses of adolescents as the main target audience regarding the redesign of this batik cakrik puppet so that it fosters the enthusiasm of the teenagers. As a result, the teenagers received well the works of wayang cakrik batik from various aspects that were important to observe, namely mainly with the visual communication design approach. A process that is no less important after this research is the development and refinement of the redesign of the batik cakrik wayang by considering the audience's response.